Early Detection of Corpus Callosum Growth Impairment in Premature Infants - J Gordon Millichap (Pediatric Neurology Briefs, 2006)
The effect of preterm birth on the serial growth of the corpus callosum and cerebellar vermis and the earliest time of detected impairment were studied by cranial ultrasonography in 61 very low birth-weight (VLBW) infants (<33 weeks gestation; <1500 gms) admitted to a single regional level III NICU from 1998 to 2000 at Christchurch Hospital, New Zealand.